Human–structure interaction effects on lightweight footbridges with tuned mass dampers - Fouli, Michael; Camara, Alfredo (Structures (Oxford), 2024)
The aim of the work is to explore how the interaction between pedestrians and a bridge deck could affect the effectiveness of tuned mass dampers (TMD) in suppressing the vibrations of lightweight footbridges. To this end, a human–structure interaction (HSI) model is built in a modal dynamic analysis framework, and it is applied to a lightweight footbridge subject to a large number of pedestrian arrangements with near-resonant walking frequencies. Compared with the response ignoring HSI, the results show that the interaction between the dynamic response of the pedestrians and the structure can reduce the vibrations in the deck, but they exceed comfort limits based on peak and root mean square (RMS) acceleration criteria. In order to reduce the oscillations to a comfortable level, a TMD located at midspan has been designed following classical optimisation methods that neglect HSI. The efficiency of the damper in resonant conditions is demonstrated in the time and frequency domains, even under a large number of synchronised pedestrians interacting with the structure, suggesting that crowds do not introduce important detuning effects in the TMD.